TRIBOLOGICAL STUDY OF THREE-BODY ABRASIVE WEAR PHENOMENON ON A356 ALUMINIUM ALLOY - Syahidah, Farah
In the process of building and maintaining an offshore platform, an assessment in the form of a structural feasibility study is required to ensure that the platform is fit for operation. The main structural feasibility studies include evaluation by in-place structural analysis, seismic, and fatigue calculations. In this Final Project, the modeling of a four-legged platform at a water depth of 55 meters located in the Java Sea is carried out. In the design process, a structural feasibility study is conducted with in-place, seismic, fatigue analysis, as well as a special task of calculating the structural strength reserve (pushover). The platform feasibility study was evaluated with SACS software with standards in accordance with API RP 2A 22nd Edition and AISC - Steel Construction Manual 15th Edition. The study begins with an inplace analysis to ensure the structure can withstand loads during operation, both gravity loads, environmental loads, and loads during extreme environmental conditions. Furthermore, structural evaluation by seismic analysis is checked for SLE and DLE condition to estimate the strength of the structure against ground motion at the installation site. Then proceed with fatigue analysis to estimate the risk of failure, damage, and age of a structure caused by cyclic loads. Furthermore, pushover analysis will be carried out in each lateral direction due to earthquake loads (seismic pushover) to find the reserve strength capacity of the structure when an earthquake occurs. Based on the results of inplace, seismic, and fatigue analysis, the structure has met all API RP 2A criteria so that it is categorized as feasible to operate. In the pushover analysis, it is known that the Reserve Stregth Ratio (RSR) in the X+ lateral is 6.20, in the X- lateral direction is 6.53, in the Y+ lateral direction is 6.34, and in the Y- axis is 6.35. So that the structure has a high reserve capacity in the event of an earthquake and has met the API RP 2A criteria. The cause of the collapse in the analyzed structure is that there are several members in the leg and pile that have been plasticized so that the displacement value becomes large then the structural strength decreases until it finally causes collapse.